17. DESCRIPTION OF NEED MATERNAL CARE FOR PREGNANT WOMEN AFTER CESAREAN AT NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY 2022- 2023 (Vietnam Journal of Community Medicine, 2023)
Objectives: Description of the need for maternal care after cesarean section at the National Hospitalof Obstetrics and Gynecology in 2022- 2023. Method: The cross-sectional descriptive study design,prospective study, combining quantitative and qualitative research on 385 women who had a cesareansection on August 1, 2022, and midwives and nurses working at the National Hospital of Obstetricsand Gynecology. Use pre-designed questionnaires for interviewing and visiting pregnant women.Organize group discussions with nurses and midwives. Results: There are 91.4%; 46.5% of pregnantwomen want to have family members; health care workers after cesarean.The percentage of pregnant women wishing to have two caregivers is the highest (82.1%). Therefore,83.1% of pregnant women require the post-operative service room. The need for post-operativecare support of pregnant women is very high, with which child care and monitoring accounts forthe highest rate of 65.2%; breastfeeding is 57.9%; exercise and rehabilitation accounted for 43.6%and personal hygiene accounted for 45.2%. The percentage of pregnant women who want postoperative care services is high, such as incision plasma projection (93.5%), breast massage (79.7%)and perineal steaming (28.6%). There are 90.1% and 77.9% of women, respectively, who want theservices of umbilical cord plasma projection and neonatal massage after surgery. Conclusion: Theneed for care of pregnant women after cesarean section is increasing, including the need for respectfor the mother and the newborn.
Keywords: Post-operative pregnant women, need of care.